Effect of injection timing to performance of a diesel engine fuelled with different diesel–ethanol mixtures. (1st August 2015) - Murcak, Ahmet; Haşimoğlu, Can; Çevik, İsmet; Kahraman, Hüseyin
Highlights: Engine performance parameters have been improved with ethanol addition. Engine performance parameters have been improved with the increase of the injection advance. The optimum performance values have been obtained for 5% ethanol addition for the injection advance of 35 KMA. Abstract: The aim of this study is to determine the effect of injection timing to performance of a single cylinder diesel engine. The fuel mixtures have been prepared by addition of ethanol to HC based diesel fuel at the ratios of 5%, 10% and 20% by volume. To change the injection timing an adjustable cam mechanism has been connected to the test engine. The results showed that; the maximum engine power has been obtained in 2400 rpm for 5% diesel–ethanol mixture at the injection advance of 35 CA. The maximum engine torque has been obtained in 1200 rpm for 5% diesel–ethanol mixture at the injection advance of 25 CA. The minimum brake specific fuel consumption has been obtained in 1000 rpm at the injection advance of 35 CA for the same mixture.